Cooptarea elitei locale în Basarabia: explorarea strategiilor imperiale în perioada 1812–1828 [Articol] - Boțolin, Sergiu (Lexon-Prim, 2023)
This study presents a comprehensive analysis of strategies aimed at co-opting the local elite, deemed a fundamental component in the governance of the Bessarabia post-1812. It seeks to reinforce and enhance the policy of integrating Bessarabia into the political, economic, and social frameworks of the Russian Empire. A central focal point of this discourse is the imperial system of noble privileges, which was extended to include the Bessarabian elite and had a substantial impact on regional dynamics. The study delves into how these privileges were employed to attract local elites and secure their support and allegiance. Furthermore, it explores facets concerning the integration of the elite into the service of the Russian Empire and the formalization of this alliance.
The co-optation of the local elite in Bessarabia: exploring imperial strategies in the period 1812-1828
Keywords: Russian Empire; nobility; Bessarabia